The story of creativity: from divine act to the creative industry - Zekrgoo, Amir Hossein (Penerbit Academi Seni Budaya Warisan Kebangsaan (ASWARA), 2016)
Art is the niche of every civilization. Here we use the term ‘Art’ in the broader meaning of the word, which includes a wide range of creative activities that comprise visual and performing arts, architecture, music and literature,. In this sense, art projects a refined manifestation of a culture; an honest representation of the degree of intellectual growth and of spiritual maturity that a people possess. It is through art that a culture can be represented in its totality; it is with art that a culture can preserve its identity; and it is through art that a civilization will be remembered and evaluated, even after its extinction.